2014
DOI: 10.1002/2014gl059393
|View full text |Cite
|
Sign up to set email alerts
|

Little late Holocene strain accumulation and release on the Aleutian megathrust below the Shumagin Islands, Alaska

Abstract: Can a predominantly creeping segment of a subduction zone generate a great (M > 8) earthquake?Despite Russian accounts of strong shaking and high tsunamis in 1788, geodetic observations above the Aleutian megathrust indicate creeping subduction across the Shumagin Islands segment, a well-known seismic gap. Seeking evidence for prehistoric great earthquakes, we investigated Simeonof Island, the archipelago's easternmost island, and found no evidence for uplifted marine terraces or subsided shorelines. Instead, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Hutchinson and Crowell (2007) suggested that six episodes of village abandonment, inferred from archaeological stratigraphy throughout the region, may have been caused by subsidence or tsunamis accompanying great earthquakes. Approximately 250 km west of Chirikof Island, Witter et al (2014) could not find clear evidence of any high tsunamis in the past 3000 yr, despite Russian accounts of severe flooding during the 1788 tsunami.…”
Section: Tsunami Recurrencementioning
confidence: 83%
See 2 more Smart Citations
“…Hutchinson and Crowell (2007) suggested that six episodes of village abandonment, inferred from archaeological stratigraphy throughout the region, may have been caused by subsidence or tsunamis accompanying great earthquakes. Approximately 250 km west of Chirikof Island, Witter et al (2014) could not find clear evidence of any high tsunamis in the past 3000 yr, despite Russian accounts of severe flooding during the 1788 tsunami.…”
Section: Tsunami Recurrencementioning
confidence: 83%
“…Although it is unclear if reports of severe flooding in the western part of the ruptured zone occurred following the 21 July earthquake or the later 6 August earthquake, 1 or 2 high tsunamis (reported run-up heights range from 3 to >30 m) caused much damage and many deaths from Kodiak Island to Sanak Island ( Fig. 1; Lander, 1996;Ryan et al, 2012b;Witter et al, 2014). The highest tsunami inundation at Southwest Anchorage was probably on 21 July, when the tsunami severely flooded Three Saints Harbor on Kodiak Island, 215 km to the northeast.…”
Section: Historical Tsunamismentioning
confidence: 99%
See 1 more Smart Citation
“…Atwater and Hemphill-Haley, 1997;Hayward et al, 2006;Kelsey, 2015;Nelson, 2015;Nelson et al, 1996;Witter, 2015) debate moved on to questions critical for hazard assessment, emergency planning and international building code design (Mueller et al, 2015;Wesson et al, 2007). Key questions include the extent of past great earthquake ruptures (a proxy for magnitude), the identification of the boundaries between rupture segments, the persistence of these boundaries over multiple earthquake cycles, recurrence intervals of great earthquakes in each segment, the role of aseismic slip, and whether segments of plate boundaries that are currently creeping can generate great earthquakes Goldfinger et al, 2012;Hayward et al, 2015;Kelsey et al, 2015;Mueller et al, 2015;Scholz, 2014;Witter et al, 2014).In order to address these questions, coastal paleoseismology continues to seek evidence to discriminate between alternative hypotheses. This inevitably results in returning to the field evidence and the quantifiable resolution of the age, the extent, and the pattern of vertical surface displacement of each rupture.…”
mentioning
confidence: 99%
“…Kodiak model estimates the age of the event to AD 1440-1620 (Figure 2c were two earthquakes in 1788 (Briggs et al, 2014). Opinions range from one great earthquake on 22 131…”
Section: Introduction and Aims 26mentioning
confidence: 99%